Fabrication and Characterization of High Performance Intermediate Temperature Alumina Substrate Supported Micro-Tubular SOFCs. Issue 7 (3rd May 2017) - Ren, Chunlei; Gan, Yun; Yang, Chunyang; Lee, Myongjin; Dong, Guohui; Xue, Xingjian
Abstract : The central challenge of solid oxide fuel cell (SOFC) technology lies in how to achieve sufficient robustness and reliability while significantly reducing system and operating cost. This paper studied a novel alumina substrate supported micro-tubular SOFC with high performance at intermediate temperatures. An in-house built extrusion system in combination with modified phase-inversion method was used to fabricate micro-tubular alumina substrate with radially well-aligned micro-channel array. The gas permeability of such an alumina substrate reached 69.2 × 10 5 Lm −2 h −1, approximately ten times that of the substrate with conventional microstructures. The addition of NiO (10 wt%) sintering aid significantly improved the bending strength of α-Al2 O3 substrate while forming NiAl2 O4 spinel phase in the substrate. Built upon the fabrication of alumina substrate, anode electrode and electrolyte layers were fabricated through dip-coating and sintering process alternatively. A porous barrier layer strategy was employed to inhibit NiO in the anode layer from diffusing into the substrate during high temperature sintering process. The resulting dense electrolyte layer and anode functional layer with the thickness of ∼10 μm and ∼20 μm were obtained respectively. The alumina substrate supported micro-tubular SOFC with material system NiO-SDC/SDC/PrBaCo2 O5+δ demonstrated the peak power density of ∼1420 mW cm −2 at 600°C, which is among the best performance of SOFCs with the same material system in open literature. The novel micro-tubular cell also demonstrated excellent thermal cycling stability. By replacing the high-cost rare-earth anode material with low-cost alumina, the novel design not only significantly reduced the cost but also improved the robustness and reliability of SOFCs.